Surface Tension of Binary Mixtures of 1-Alkyl-3-MethylImidazolium Bis(trifluoromethylsulfonyl)imide Ionic Liquids with Alcohols - Andreatta, Alfonsina Ester (2014)
New experimental surface tension data have been provided at 283.15, 298.15, 313.15 K and atmospheric pressure for binary mixtures of 1-butyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide and 1-octyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide ionic liquids with the alcohols: methanol, ethanol, 1-propanol, 2-propanol, l-butanol and 1-pentanol. The experimental results show that the surface tensions of these mixtures depend systematically on the alkyl chain length of the ionic liquid and alcohol, composition and temperature. Surface tension changes on mixing have been calculated and adequately fitted by the Redlich–Kister polynomial equation. The adjustable parameters and the standard deviations between experimental and calculated values are reported.